Management of drug hypersensitivity in the pediatric population. Issue 10 (2nd October 2016) - Atanaskovic-Markovic, Marina; Caubet, Jean-Christoph
ABSTRACT: Introduction : Several recent studies confirmed that drug allergy in children is over diagnosed, which is a major public health problem, and results in use of alternative drugs, increasing resistance and health costs. Areas covered : Articles in English with data on drug hypersensitivity in children were identified by searching the databases of MEDLINE (National Library of Medicine) from 1990 till 2016. Expert commentary : It is crucial to make a precise diagnosis with performing a complete allergy work-up based on carefully selected diagnostic tests depending on whether an immediate or a non-immediate reaction is suspected. The drug provocation test remains the gold standard in diagnostic drug hypersensitivity in children.